Is the Children’s 15-Minute City an Effective Framework for Enhancing Children’s Health and Well-Being? An Empirical Analysis from Western China - Xiao Wang; Jingping Huang; Zhengyou Qin; Wei Gan; Zhen He; Xiang Li (Buildings)
Increasing attention is being directed toward understanding the impact of urban built environments on children’s health. The concept of the 15-minute city, or “15-minute life circle”, in China is significant; however, the needs of the pediatric population are often overlooked. Walkability and accessibility to urban service facilities are crucial for promoting children’s well-being. This paper focuses on the old city of Guilin in western China as a case study. It investigates the service facilities within a 15-minute life circle that affect children’s physical health, mental health, and social engagement. Utilizing the Walking Index method, this study assesses the walkability and rationality of these facilities in 621 neighborhoods. Data were gathered from 200 questionnaires and interviews with children, concentrating on their daily use of these facilities, supplemented by a multi-source analysis. The findings reveal that the Walking Index in the study area is generally low, with an uneven distribution, primarily influenced by road network density, block size, and urban landscape patterns. This study proposes the development of a “Children’s Healthy 15-minute Life Circle”, which would increase child-friendly service facilities, pedestrian infrastructure, and urban road network density. It also advocates for constructing service facilities that enhance children’s health and the optimization of the spatial arrangement of these facilities. Furthermore, it suggests the effective utilization of urban landscapes to create a diverse system of leisure spaces for children. This study offers valuable insights for enhancing the walkability of urban life circle service facilities and establishing a child-friendly city.